PENGARUH GAYA KOGNITIF DAN GENDER TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Murtafiah Murtafiah; Nursafitri Amin (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThe aim of this research is to determine the effect of cognitive style and gender on mathematical problem solving ability. This research is an expost facto research. The students of Mathematics Education Department of Universitas Sulawesi Barat who program the trigonometric course were made population in this research. Data were collected by documentation dan test techniques. Documentation was used to obtain data of gender. GEFT test and problem solving ability test were used by researcher. The technique of data analysis used multiple linear regression analysis. The results showed that (a) cognitive style influenced the mathematical problem solving ability with significantly; (b) gender has no effect on the mathematical problem solving ability; (c) cognitive and gender styles together have a significant effect on mathematical problem-solving ability. Keywords: Cognitive Style, Gender, Mathematical Problem Solving Ability